2021
DOI: 10.1038/s41467-021-25509-3
|View full text |Cite
|
Sign up to set email alerts
|

New-onset IgG autoantibodies in hospitalized patients with COVID-19

Abstract: COVID-19 is associated with a wide range of clinical manifestations, including autoimmune features and autoantibody production. Here we develop three protein arrays to measure IgG autoantibodies associated with connective tissue diseases, anti-cytokine antibodies, and anti-viral antibody responses in serum from 147 hospitalized COVID-19 patients. Autoantibodies are identified in approximately 50% of patients but in less than 15% of healthy controls. When present, autoantibodies largely target autoantigens asso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
376
8
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 371 publications
(435 citation statements)
references
References 61 publications
37
376
8
14
Order By: Relevance
“…In the observation with the context of severe COVID-19, numerous antibody secreting cells are produced as a result of upregulation of extrafollicular B cells, including clonotypes that are autoreactive ( Woodruff et al, 2020 ). Considering these data in cellular structuring, ANA was detected in 18% of COVID-19 patients in our study, but this was lower than the data in the literature (21.3%–64%) ( Pascolini et al, 2021 ; Gazzaruso et al, 2020 ; Lerma et al, 2020 ; Sacchi et al, 2020 ; Chang et al, 2021b ; Chang et al, 2021a ; Trahtemberg et al, 2021 ). The relationship between disease severity or the time of sampling and antibody titers were not significant, but the majority of ANAs were strongly positive at a titer of 3+.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…In the observation with the context of severe COVID-19, numerous antibody secreting cells are produced as a result of upregulation of extrafollicular B cells, including clonotypes that are autoreactive ( Woodruff et al, 2020 ). Considering these data in cellular structuring, ANA was detected in 18% of COVID-19 patients in our study, but this was lower than the data in the literature (21.3%–64%) ( Pascolini et al, 2021 ; Gazzaruso et al, 2020 ; Lerma et al, 2020 ; Sacchi et al, 2020 ; Chang et al, 2021b ; Chang et al, 2021a ; Trahtemberg et al, 2021 ). The relationship between disease severity or the time of sampling and antibody titers were not significant, but the majority of ANAs were strongly positive at a titer of 3+.…”
Section: Discussioncontrasting
confidence: 89%
“…Although various ANA patterns have been detected in the initiation of COVID-19, the presence of patterns directed mainly against nuclear antigens has been reported ( Lerma et al, 2020 ; Chang et al, 2021b ; Chang et al, 2021a ). In agreement with the literature, mainly nucleolar patterns were detected in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have demonstrated the significant breadth of emerging autoreactivity in severe SARS-CoV-2 infection [1][2][3] . More specifically, we have identified a relaxation of peripheral tolerance within early antibody secreting cells that emerge in patients with COVID-19 as important drivers of those responses 2 .…”
Section: Main Textmentioning
confidence: 99%